Relationship between the maximum particle sizes in motion and the maximum water discharges associated with the movement of those sizes. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fac. of Geography Gadjah Mada Univ., 2001)
If the size distribution is narrow, both the smallest and largest particles are set in motion by forces of similar magnitude. In this way the entire bed begins to move at more or less one flow discharge. If the size distribution is wide, the forces required to entrain the smaller and the larger particles are significantly different. There are several important aspects in which the initial motion problem for non-uniform sediments differs from that for uniform sediment. The grain diameter is the only particle length scale in the problem for uniform sediment. The non- uniform case, on the other hands, has two length scales. The diameter of the particular size fraction of interest is the length scale for the particle forces of lift, drag, and gravity, specifically as it governs how far, into the flow the grain protrudes. The presence of these two length scales in the equation for critical shear stress for sediment on uniform-and non-uniform beds. Data collected by the Author in July 1990 at Pitzbach, Austria (Inpasihardjo, 1991) and collected by the teams from the British Institute of Hydrology and Colorado State University at the Roaring River, upstream and downstream sites in 1984 and 1985 were analyzed using two techniques to obtain the relationship between the largest bed load clast in motion and unit water discharge associated with movement of those clasts using two techniques. The results show that, as expected, there is a positive relationship between the movement of large clast and the water discharge. However, for the individual measurements the relationship is weak A possible cause of the weakness of the relationship is that since the largest clasts move irregularly and non-uniformly, it is a matter of chance whether an individual bed load measurement lasting 2 â 20 minutes traps the overall maximum size in motion. From the discussion the second technique gives a smaller diameter being moved at the same discharge than does the first technique. This is probably caused by the different number of data points provided by the two techniques (the second technique gave more data points than the first technique).